All Days 2001
DOI: 10.4043/13050-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of Leak Resistance in Industry Standard OCTG Connections using Finite Element Analysis and Full Scale Testing

Abstract: The original American Petroleum Institute (API) tubular specifications were established in the early 20th century with the intent to standardize pipe sizes and connections so that material from one mill/user could be assembled with material from other sources. The original API specifications for threaded connections did not focus specifically on ensuring leak resistance-only interchangeability. Today, the importance of connection integrity and reliable leak resistance is more widely recognized. Casing and tubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Vignes & Aadnøy (63) found that leaks through steel tubing and casing accounted for most failures in offshore Norway. Schwind et al (64) observed that 90% of casing failures were attributable to faulty connections.…”
Section: Mechanisms Of Wellbore-integrity Failurementioning
confidence: 99%
“…Vignes & Aadnøy (63) found that leaks through steel tubing and casing accounted for most failures in offshore Norway. Schwind et al (64) observed that 90% of casing failures were attributable to faulty connections.…”
Section: Mechanisms Of Wellbore-integrity Failurementioning
confidence: 99%
“…1416 In addition, a weak bonding strength at the interface and poor cementing quality can cause the cement sheath to lose its barrier function. 17,18…”
Section: Introductionmentioning
confidence: 99%
“…Finite element analysis (FEA) has been applied for screening purposes by calculating, for the metal-tometal seal, the ratio of the average contact stress to applied pressure [4,5]. However, the success or failure of a metal-to-metal seal is governed by other parameters than only contact stress acting between a perfectly flat and a round surface.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of surface topography in the contact simulation allows the introduction of the concept of permeability of the (deformed) gap between the contacting areas of the pin and box of a metal-to-metal seal [10][11][12][13][14]. This permits the definition of a leakage criterion based on permeability instead of a contact stress to pressure ratio, as used in e.g., [4,5]. In addition, it allows the computation of the actual leak rate when combined with the differential pressure and fluid properties [13].…”
Section: Introductionmentioning
confidence: 99%